Fractional exhaled nitric oxide non-suppression in asthma - Couillard Castonguay, S (2021)
Background: Factional exhaled nitric oxide (FeNO) and blood eosinophils are biomarkers of the higher risk type-2 inflammatory phenotype in asthma.